Fungi associated with creosoted pine utility poles in New York - Carranza, Julieta (New York, New York : [editor no identificado], 1979)
Tesis (Master of Science)--State University of New York. College of Environmental Science and Forestry, 1979.
Keywords: PINOS -- ENFERMEDADES Y PLAGAS; HONGOS DESTRUCTORES DE LA MADERA